2019
DOI: 10.1111/jocn.15064
|View full text |Cite
|
Sign up to set email alerts
|

Oral anticancer therapy project: Clinical utility of a specific home care nursing programme on behalf of Italian Association of Medical Oncology (AIOM)

Abstract: Aims and objectives To assess the effectiveness of a specific home care nursing programme in addition to standard care in patients (pts) receiving oral anticancer treatments. Background Oral anticancer therapy present challenges for pts since treatment is a home‐based therapy. This study evaluates the potentiality of a home care nursing programme in decreasing hospital accesses for not severe toxicity. Methods This is an open‐label, multicentre, randomised trial including pts who were receiving an anticancer o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Eight RCTs and 2 quasi-experimental studies (CBA design) were included, which evaluated 2315 participants (Table 1 ). Five studies were conducted in the USA [ 11 , 17 , 41 43 ] and one each in Canada [ 14 ], France [ 38 ], Italy [ 39 ], Hong Kong [ 23 ], and Turkey [ 40 ]. Seven studies evaluated heterogeneous samples of patients with cancer, two studies included patients with lung cancer [ 40 , 43 ], and one study included women with breast cancer [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eight RCTs and 2 quasi-experimental studies (CBA design) were included, which evaluated 2315 participants (Table 1 ). Five studies were conducted in the USA [ 11 , 17 , 41 43 ] and one each in Canada [ 14 ], France [ 38 ], Italy [ 39 ], Hong Kong [ 23 ], and Turkey [ 40 ]. Seven studies evaluated heterogeneous samples of patients with cancer, two studies included patients with lung cancer [ 40 , 43 ], and one study included women with breast cancer [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most studies received funding from hospitals, universities, or national-level granting agencies [ 11 , 14 , 17 , 23 , 38 , 40 43 ]. One study reported industry funding [ 38 ], and another did not report funding [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations